Flashmob: A Heutagogical Tool for Social Learning in Entrepreneurship Education. (2nd July 2022) - Tunstall, Richard; Neergaard, Helle
The development of entrepreneurial mindsets and competencies is a key differentiator of entrepreneurship education, yet traditional, individualist, functional approaches to entrepreneurship education do not adequately support this and appropriate tools and techniques remain unclear. This learning innovation is an approach to directly support the development of entrepreneurial mindsets and competencies in entrepreneurship education through socially-situated experiential learning in a structured way. It uses flashmobs as a heutagogical entrepreneurship education technique, which engages students in self-directed learning through real social action. By careful framing around appropriate entrepreneurship theory, combined with coaching and facilitation, we show how it is possible for entrepreneurship educators to support students in developing a critical reflective appraisal of their own ways of thinking and latent entrepreneurial competencies when facing challenges that require an entrepreneurial response while simultaneously providing the platform for students to embark on their journey of entrepreneurial self-discovery through both experiential and existential learning. We contribute by providing a heutagogical tool to be used either iteratively as the launch-pad into traditional andragogical methods in new venture creation or as the embarkation into new heutagogical programs, which emphasize self-directed entrepreneurial learning.